Hacer la América: una estrategia alternativa al proceso de inserción académica en la sociología española - Morales Martín, Juan Jesús (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The initial aim of this article is to put in crisis the concept of “Spanish sociology “, since this science became institutionalized in Spain under the cultural horizon of the Franco’s regime, for from this theoretical conception to analyze the intellectual contribution of two Spanish sociologists who emigrated and did career in Latin America. The pretension is to compare the intellectual paths of one of the first social scientists that he came to Latin America after the republican exile of the Civil war, Jose Medina Echavarría’s case in Mexico, with a member of the second generation of sociologists who arrived in that continent in the decade of the 50, Juan Francisco Marsal’s case in Argentina. The comparison answers to an attempt of exploring the processes of academic insertion and the theoretical offers of both sociologists inside the scientific Latin-American field. In addition the article will realize of the differences between Medina and Marsal at the moment of reinsertarse in the sociological Spanish field at the beginning of the 70s, when the democratic winds began to erode the Franco dictatorship. But beyond the biographical and intellectual revision of both authors, this article doesn´t want to be a review of the processes of institutionalization of the Latin-American sociology either, but fundamentally it attacks to be a critical reconstruction of the sociological Spanish theory on the basis of an inclusive perspective that tries to recognize the exiled sociologist, from his marginality, and to the emigrated sociologist, from his peripheral position, as central sociologists in the recent history of the Spanish sociology.